Socioperception About Smoking Behavior In Islamic Boarding School - Hafid Algristian; Choirotussanijjah (Universitas Nahdlatul Ulama Surabaya, 2020)
Indonesia is the fifth largest tobacco producer in the world. Average cigarette consumption in adolescents over 15 years is 12 cigarettes per day. The increase in the number of smokers is influenced by internal factors and external factors. Internal factors include perception and attitude towards smoking behavior. These perceptions and attitudes determine whether someone agrees and then decides to follow the act or not. Hopefully, the more someone disagrees with smoking behavior, the lower the smoking behavior rate in adolescents. How many people at the boarding school initially refused cigarettes, but because of fear of exclusion, then turned into permissive to cigarettes. This study aims to analyze the perceptions and attitudes of Islamic boarding school alumni to smoking behavior of boarding school residents. The results of this study are expected to be self-evaluation materials as well as a starting point for re-planning counseling programs for the anti-smoking movement in Islamic boarding schools.